Sustainable extraction of Amber rice bran oil (Oryza sativa L.): a comparative study between conventional and ultrasound-assisted extraction using ethanol as solvent - Turki, S S; Mohammed, N K; Muhialdin, B J; Hussin, A S M (Institute of Physics Publishing, 2024)
Rice bran oil (RBO) is highly valued due to its unique properties. Due to environmental obstacles such as climate variation and global warming, there has been a growing interest in green extraction approaches recently, like ultrasound-assisted extraction (UAE), which offer several advantages in terms of sustainability and environmental impact such as reduced extraction period, solvent usage, and significantly increased extracted amount compared to conventional methods. This work compared oil extraction from Iraqi Amber rice bran employing ethanol as an eco-friendly solvent and two methods, traditional ethanol soaking (SEE) and ultrasound-assisted extraction (UAEE). According to the results, the oil yield by UAEE was higher than SEE, by 19.22% and 17.98%, respectively. A minor increase in the refractive index was recorded in the oil extracted using SEE, and a slight increase in the acidity and free fatty acid values in UAEE. The γ-Oryzanol in the oil extracted using UAEE was higher, reaching 5.88 mg/g. Fatty acid analysis showed that the oil extracted using SEE contained mostly linoleic acid, and UAEE had the highest value of palmitoleic acid. Using ethanol as a solvent, both techniques were generally successful in extracting oil from amber rice bran, with the UAEE method outperforming SEE.